Effect of intramuscular application of seminal plasma on alpaca’s embryo survival after copula - Turín V., Jesús (2015)
This study aimed to evaluate the effect of intramuscular application (IM) of seminal plasma on embryo survival in the alpaca after natural mating. The study was conducted in Puno, Peru. Seminal plasma was obtained from alpaca semen samples, which were collected and diluted 1:1 in phosphate buffered saline (PBS), then centrifuged and kept frozen in storage until use. Non-pregnant alpacas (n=117) were selected according to the presence of a dominant ovarian follicle (>7 mm) detected by transrectal ultrasonography. Females were naturally mated and assigned randomly into one of three groups: T1 (n=40): 1 ml of seminal plasma diluted in PBS, IM; T2 (n=39): 1 ml of GnRH analogue (0.0042 mg buserelin), IM; T3 (n=38) without administration of any product (control). Females were evaluated by transrectal ultrasonography on day 25 after mating to determine pregnancy and on day 62 for determining the embryo’s survival rate. The results showed 67.5, 51.3 and 55.3% conception rate on day 25 and 92.6, 80.0 and 85.7% of embryo’s survival rate on day 62 for groups T1, T2 and T3 respectively and without statistical differences between treatments. The results suggest that IM application of seminal plasma immediately after natural mating may increase embryo survival as compared to the application of GnRH or natural mating, however, this difference was not statistically significant.